2012
DOI: 10.1371/journal.pone.0032616
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin Loaded-PLGA Nanoparticles Conjugated with Tet-1 Peptide for Potential Use in Alzheimer's Disease

Abstract: Alzheimer's disease is a growing concern in the modern world. As the currently available medications are not very promising, there is an increased need for the fabrication of newer drugs. Curcumin is a plant derived compound which has potential activities beneficial for the treatment of Alzheimer's disease. Anti-amyloid activity and anti-oxidant activity of curcumin is highly beneficial for the treatment of Alzheimer's disease. The insolubility of curcumin in water restricts its use to a great extend, which ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
186
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 370 publications
(205 citation statements)
references
References 41 publications
13
186
0
Order By: Relevance
“…Besides changing the surfactant used in the NP synthesis, the surface of the NP can be modified by the addition of PLGA, 134 nm, oral, DMAB, 400 µg, drug, R [14] PLGA, 177 nm, PVA, i.v., 20 µg, EF, R [17] PLGA, 200 nm, PVA, c.a., 5 mg, EF, R [18] PEG-PLA, 100 nm, none, i.v., 0.6 mg, EF, M [27] PLA, 300 nm, PVA, i.v., 1.125 mg, radioactive drug, M [31] PLGA, 187 nm, F68, i.v., 13.6 µg, EF, R [32] PLGA, 239 nm, n/r, i.v., 82.5 µg, EF, R [36] 25 30 other compounds, such as chitosan or PEG, in an attempt to improve brain NP uptake (Table 2 ). TPGS has been successfully used to prepare NPs, and it was found that TPGS was a more effective and safer emulsifier than PVA, and could improve adsorption of NPs by the gastrointestinal tract [23] .…”
Section: Brain Uptakementioning
confidence: 99%
See 3 more Smart Citations
“…Besides changing the surfactant used in the NP synthesis, the surface of the NP can be modified by the addition of PLGA, 134 nm, oral, DMAB, 400 µg, drug, R [14] PLGA, 177 nm, PVA, i.v., 20 µg, EF, R [17] PLGA, 200 nm, PVA, c.a., 5 mg, EF, R [18] PEG-PLA, 100 nm, none, i.v., 0.6 mg, EF, M [27] PLA, 300 nm, PVA, i.v., 1.125 mg, radioactive drug, M [31] PLGA, 187 nm, F68, i.v., 13.6 µg, EF, R [32] PLGA, 239 nm, n/r, i.v., 82.5 µg, EF, R [36] 25 30 other compounds, such as chitosan or PEG, in an attempt to improve brain NP uptake (Table 2 ). TPGS has been successfully used to prepare NPs, and it was found that TPGS was a more effective and safer emulsifier than PVA, and could improve adsorption of NPs by the gastrointestinal tract [23] .…”
Section: Brain Uptakementioning
confidence: 99%
“…P188 was demonstrated to be a better brain targeting agent for PLGA NPs than P80 after intravenous administration in several reported studies [15,17,19,43] . PLA NPs [31] TAT-PLA NPs [31] PLGA NPs [32] g7-PLGA NPs [32] SA-g7-PLGA NPs [32] PLGA NPs [36] TPGS-PLGA NPs [36] Tf-TPGS-PLGA NPs [36] PEG-PLGA NPs [41] Lf-PEG-PLGA NPs [41] Percentage (%) brain uptake of lignad-conjugated nanoparticles…”
Section: Therapeutic Efficacymentioning
confidence: 99%
See 2 more Smart Citations
“…The research of curcumin encapsulated that poly lactic-co-glycolic acid (PLGA) nanoparticles can destroy amyloid aggregates, exhibit antioxidative property, and are non-cytotoxic. The encapsulation of the curcumin in PLGA does not destroy its inherent properties and so, the PLGA-curcumin nanoparticles can be used as a drug with multiple functions in treating Alzheimer's disease [24].…”
Section: Resultsmentioning
confidence: 99%